2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26595
|View full text |Cite
|
Sign up to set email alerts
|

Cranking Up Cornerstone: Lessons Learned from Implementing a Pilot with First-Year Engineering Students

Abstract: This paper presents evidence-based practice in required first-year engineering curriculum at Northeastern University. It will outline the motivation to redesign the curriculum, and include review of engineering education practice that inspired and directed the change, along with evidence and assessment of the effectiveness of the new approach. In 2012, after a comprehensive curriculum review by a faculty committee at Northeastern University, the firstyear engineering program decided to adopt the "cornerstone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Cornerstone of Engineering is in its fourth full year of iteration at Northeastern University. Through benchmarking and iteration, we have learned how to weave programming and design concepts into one course, creating an interdisciplinary learning experience for our first-year students [10]. The culture necessary to support this effort has also evolved over time with the course taking on two versions, both of which are supported by personnel and equipment in our First-Year Engineering Learning and Innovation Center [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cornerstone of Engineering is in its fourth full year of iteration at Northeastern University. Through benchmarking and iteration, we have learned how to weave programming and design concepts into one course, creating an interdisciplinary learning experience for our first-year students [10]. The culture necessary to support this effort has also evolved over time with the course taking on two versions, both of which are supported by personnel and equipment in our First-Year Engineering Learning and Innovation Center [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several universities have implemented the full-year cornerstone model successfully and have observed its impacts on first-year students. Seminal research has shown that successful cornerstone classes focus their first semester on instilling the fundamentals of engineering [1][2][3][4]. This includes the engineering design process, design software and programming, project management, and teamwork.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Northeastern University's cornerstone consists of two semesters, where the first semester focuses on engineering principles and the second semester focuses on the application of those principles through design projects [1,2]. Notre Dame's college of engineering employs a two semester long cornerstone that encourages students to design and prototype a drone-like device in the first semester.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations